Testing of the January Effect on The Indonesia Stock Exchange - Nadia Latifa; Siti Atikah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to look at the January effect phenomenon in the LQ45 stock group on the Indonesia Stock Exchange during the 2020-2022 observation period. The January effect phenomenon is an anomaly that presents the phenomenon of increasing stock prices in January. The variables used are abnormal returns and trading volume activity. The sample consisted of 30 companies in the LQ45 index group on the Indonesia Stock Exchange. The sampling method is purposive sampling. The analytical tools used in this research are the paired sample t-test and the Wilcoxon Sign Test. The results of the research analysis show that there is no significant difference between abnormal returns and trading volume activity in the first 5 days of January and the last 5 days before January in the 2020-2022 period. Overall, there is no January effect phenomenon in the LQ45 stock group on the Indonesia Stock Exchange in terms of abnormal returns and trading volume activity.